James Joyce a literary companion - Broderick, James F. 1963- (McFarland & Company, Inc., Publishers, 2018)
"This literary companion guides readers through James Joyce's four major works...Dubliners, A Portrait of the Artist as a Young Man, Ulysses and Finnegans Wake...with chapter-by-chapter discussions. An A to Z format covers the works, people, history and context that influenced his writing. Appendices summarize notable Joycean literary criticism and biography, and significant films"...
Includes bibliographical references and index
Keywords: Joyce, James -- 1882-1941 -- Criticism and interpretation; Joyce, James -- 1882-1941